High-capacity organic sodium ion batteries using a sustainable C4Q/CMK-3/SWCNT electrode. Issue 8 (11th June 2019) - Yan, Bing; Wang, Lijiang; Huang, Weiwei; Zheng, Shibing; Hu, Pandeng; Du, Yuyu
Abstract : SWCNTs formed a three-dimensional conductive network between C4Q/CMK-3 nanocomposites, significantly improving the electrochemical performance of C4Q-SIBs. Abstract : Calix[4]quinone (C4Q) is a high-capacity organic cathode material, but its solubility in conventional organic electrolytes causes capacity decay, which leads to unavoidable restrictions in the practical application. Our previous research has revealed that the dissolution of C4Q can be effectively restricted by encapsulating it in CMK-3, but there is still room for improvement in its circulation performance and rate capability. Herein, we prepared a series of C4Q/CMK-3/SWCNT composites for sodium ion batteries (SIBs) by a facile deaerating–stirring method. The C4Q/CMK-3/SWCNT (40 wt%, 40 wt%, 10 wt%) cathode delivers a high and stable discharge capacity (290 mA h g −1 ) after 100 cycles at a current rate of 0.1 C. Even at a high rate of 1 C, its capacity is 346 mA h g −1 . The stability and electronic conductivity of C4Q/CMK-3/SWCNTs are intensified by the three-dimensional conductive network. Furthermore, the redox properties and sodium storage average potential platform of C4Q are first calculated by density functional theory (DFT).